Legal Protection Towards Public Companies from Bankruptcy - Tranggono, Emiral Rangga; Silalahi, Udin; Shubhan, Hadi (Universitas Pelita Harapan, 2024)
Law Number 37 of 2004 on Bankruptcy and Suspension of Debt Payment Obligations (UU KPKPU) only requires the provision that a Bankruptcy/PKPU application to be submitted by one creditor, and that it can be proven that the public company has at least two creditors, one of which is past due. Financial Services Authority (OJK) has the authority to regulate and supervise activities in the capital market field or sector carried out by public companies. OJK should be responsible for providing legal protection for public companies that submit applications for bankruptcy. The research method used is a normative legal research method. The results of this research confirm that Article 55 paragraph (1) of the OJK Law and Article 8 paragraph 4 of Law Number 4 of 2023 on the Development and Strengthening of the Financial Sector (P2SK Law) are the legal basis or legal protection that gives the authority to the Financial Services Authority to carry out regulation and supervision of financial services activities in the capital markets sector, where financial services activities in the capital markets sector are also carried out by public companies. There must be rules that are made firmly and explicitly so that the OJK is given responsibility, function and authority in protecting public companies from bankruptcy by carrying out insolvency tests. This means that before a public company is submitted for bankruptcy, the OJK must first carry out an insolvency test to determine whether the public company is in a state of insolvency or is actually in a state of solvency. If the results state that the public company is indeed insolvent, then the OJK must provide a product stating either in the form of a cover letter or a certificate that the public company is suitable for the debtor to submit a bankruptcy petition.